2009
DOI: 10.4103/0028-3886.55598
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in neurosurgical intraoperative consultation

Abstract: The discrepant cases need to be reviewed regularly by pathologists to familiarize themselves with the morphological changes and artifacts. The knowledge of possible errors could minimize misinterpretation and help in providing a more conclusive opinion to the operating surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 9 publications
3
21
0
Order By: Relevance
“…Intraoperative consultation of brain lesions are requested to differentiate neoplastic from reactive lesions; to differentiate metastatic from primary lesions; to estimate the degree of malignancy and to determine the tumor margins. 7,8 Diagnostic accuracy (88%) achieved in the present study were comparable with the series of other studies (86% to 97%). 4,[9][10][11] Most of the gliomas were easily identified in the smears.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Intraoperative consultation of brain lesions are requested to differentiate neoplastic from reactive lesions; to differentiate metastatic from primary lesions; to estimate the degree of malignancy and to determine the tumor margins. 7,8 Diagnostic accuracy (88%) achieved in the present study were comparable with the series of other studies (86% to 97%). 4,[9][10][11] Most of the gliomas were easily identified in the smears.…”
Section: Discussionsupporting
confidence: 91%
“…As Gliomas could be heterogeneous, many studies have also concluded that it would be unwise to grade the tumors in every cases in rapid diagnosis. 1,7,10,12 In the study conducted by Jennifer et al, the most common and distinctive findings in 23 cases of pilocytic astrocytoma were markedly elongated bipolar cells, Rosenthal fibers and eosinophillic granular bodies. 13 All these features were evident in our case of pilocytic astrocytoma ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are no freezing artifacts. It is simple rapid, reliable and inexpensive[8] However, it also has limitations; that is, tissue architecture is not apparent and with firm tissue, smear preparation becomes a difficult task. The utility of the imprint/squash preparation technique could be beneficial in centers where a facility for frozen sections is unavailable, in case of a power break-down, or a lack of trained technical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of the imprint/squash preparation technique could be beneficial in centers where a facility for frozen sections is unavailable, in case of a power break-down, or a lack of trained technical personnel. [8]…”
Section: Discussionmentioning
confidence: 99%
“…However, intraoperative consultation for spinal lesions by crush smear cytology can provide a preliminary diagnosis so that surgeon can decide further management on the operating table. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%